2019
DOI: 10.3390/app9142905
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of a Three-Dimensional Printed Porous Media Produced by Selective Laser Melting Technology for the Optimization of Loop Heat Pipe Wicks

Abstract: The primary wick in a loop heat pipe device is a key component that is central to the operation of the device. Both high permeability and capillary pumping capacity, two properties highly dependent on wick structure, are strongly desirable for a satisfactory thermal performance. In this paper, selective laser melting (SLM), a three-dimensional (3D) printing technology, is used to create a primary wick for an 80 W heat transfer application. The permeability and capillarity values of this wick, experimentally me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Owing to its porous structure, multiple streams of fluids can be simultaneously achieved in a single volume, demonstrating excellent potential for the parallelization of multiple fluid channels and high interfacial areas that facilitate mixing/reaction processes 9 . Although efforts have been made to advance the fundamental understanding of the fluid transport processes in the micro-architected materials with lattice structures 4,[10][11][12] , most investigations have focused on single-phase flow. A recent notable work by Dudukovic et al 9 demonstrated the precise manipulation of multi-phase flow in the open lattice structures, where capillary-driven fluid flow along preferential pathways is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its porous structure, multiple streams of fluids can be simultaneously achieved in a single volume, demonstrating excellent potential for the parallelization of multiple fluid channels and high interfacial areas that facilitate mixing/reaction processes 9 . Although efforts have been made to advance the fundamental understanding of the fluid transport processes in the micro-architected materials with lattice structures 4,[10][11][12] , most investigations have focused on single-phase flow. A recent notable work by Dudukovic et al 9 demonstrated the precise manipulation of multi-phase flow in the open lattice structures, where capillary-driven fluid flow along preferential pathways is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the printed capillary wick cloud enhanced the heat transfer performance of the heat pipe with an increase in the capillary size according to h ( t )– t (1/3) in the intermediate stage, although gravity affected the rise of liquid in the capillary wick. Esarte et al (2019) designed and 3D-printed a frame-type 316 stainless steel capillary wick porous structure for an LHP with a heat transfer requirement of 80 W and experimentally tested its permeability and capillary rise height. The results showed that the permeability of an SLM capillary wick is two orders of magnitude greater than that of a powder-sintered capillary wick.…”
Section: Introductionmentioning
confidence: 99%